Strategi Manajemen Lalu Lintas Di Kawasan Pantai Gandoriah Pariaman - Busnia, Adib Isra Mudrah; Purnawan, Purnawan (Universitas Andalas, 2024)
The attraction of tourism in Pariaman City is very high for both local and foreign tourists. One of the famous tourism areas in Pariaman City is Gandoriah Beach. Based on data obtained from BPS Pariaman City, the number of tourists visiting in 2020 was 112,278 people. In 2021 the number of tourists increased to 255,561 people. The increase in tourist visits can cause an increase in traffic volume, which can cause congestion, discomfort, and can endanger safety. Therefore, it is necessary to identify what traffic problems occur in the Gandoriah Pariaman Beach tourist area and find the right traffic management solution for the existing problems. The methodology of this study is to analyze traffic performance in the Gandoriah Beach area with indicators of V/C ratio, speed, density, and road service level. The analysis was carried out by analyzing data obtained in the field and grouping existing problems and solving traffic problems appropriately based on existing guidelines. Furthermore, an analysis was also carried out on the capacity of the available parking lot and on-street parking and an analysis of pedestrian facilities. From the analysis results, it can be concluded that the best handling in the Gandoriah Beach area for the problem of road network performance, the right handling is to regulate street vendors, provide no-stop signs, and provide sidewalk barriers. To handle parking problems, namely arranging parking by moving on-street parking and limiting parking hours. While handling the problem of pedestrian facilities is to rebuild and widen the sidewalk and provide decent crossing facilities for pedestrians.